Економічна поляризація та цифрова трансформація ринку праці: роль штучного інтелекту - Логвіненко, Б.І. (Економіка промисловості, 2025)
Статтю присвячено визначенню впливу автоматизації та технологій штучного інтелекту на структуру праці та явище економічної поляризації в умовах цифрової трансформації ринку праці. Мета — перевірити гіпотезу, згідно з якою модель співпраці людини та штучного інтелекту є найбільш ефективною та безпечною траєкторією суспільного розвитку. На основі комплексного підходу проаналізовано сучасні теоретичні концепції, а також проведено власне онлайн-опитування серед української молоді. Підтверджено, що потенціал штучного інтелекту (ШІ) може бути використаний в економіці України для прискореного зростання лише за умови інвестування в людський капітал і формування кадрів, здатних ефективно співпрацювати з технологіями. The study is devoted to identifying the impact of automation and artificial intelligence technologies on the labor structure and the phenomenon of economic polarization in the context of the digital transformation of the labor market. Its objective is to test the hypothesis that the human — AI collaboration model represents the most effective and safe trajectory for societal development. A comprehensive approach was applied to analyze contemporary theoretical concepts, global research, and empirical data, complemented by an original online survey conducted among Ukrainian youth (92 respondents). The first part of the research defines the conceptual framework and examines the phenomenon of labor market polarization, whereby technological progress leads to a decline in medium-skilled positions, while demand concentrates in high- and low-skilled segments. Risks to social structure and economic stability are outlined, supported by historical examples (the USA and Europe after the 1980s) and modern forecasts. The empirical stage included designing a questionnaire and conducting a survey that covered access to technology, digital skills, attitudes toward artificial intelligence, motivational barriers, and migration intentions. The results indicate a high level of technical access among young people but also a formal attitude toward learning. Nearly half already use AI services (ChatGPT, Copilot); however, their understanding of the technology remains moderate. It was determined that, to ensure Ukraine’s sustainable economic development, the education system and labor market must reorient toward training specialists capable of creating and maintaining modern technologies (engineers, analysts, data specialists), as well as developing sectors where the human component remains critical — education, healthcare, and creative industries. The findings confirm that Ukraine’s economy can harness the potential of artificial intelligence for accelerated growth only if investments are made in human capital and in developing a workforce capable of effective collaboration with technology; otherwise, there is a risk of increased outmigration of skilled workers. The Human + AI model offers Ukraine the opportunity to leapfrog intermediate stages of industrial development and build a “smart” economy from the outset — a particularly vital advantage during post-war recovery, where deploying robotics for infrastructure reconstruction, implementing AI systems in urban governance, and creating new high-skilled jobs can generate rapid economic gains and sustainable growth.